h - Daniilidis, Kostas; Maragos, Petros; Paragios, Nikos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The six-volume set comprising LNCS volumes 6311 -- 6316 constitutes the refereed proceedings of the 11th European Conference on Computer Vision, ECCV 2010, held in Heraklion, Crete, Greece, in September 2010. The 325 revised papers presented were carefully reviewed and selected from 1174 submissions. The papers are organized in topical sections on object and scene recognition; segmentation and grouping; face, gesture, biometrics; motion and tracking; statistical models and visual learning; matching, registration, alignment; computational imaging; mutli-view geometry; image features; video and event characterization; shape representation and recognition; stereo; reflectance, illumination, color; medical image analysis.
Computational Imaging -- Guided Image Filtering -- Analysis of Motion Blur with a Flutter Shutter Camera for Non-linear Motion -- Error-Tolerant Image Compositing -- Blind Reflectometry -- Photometric Stereo for Dynamic Surface Orientations -- Fully Isotropic Fast Marching Methods on Cartesian Grids -- Spotlights and Posters M1 -- Descattering Transmission via Angular Filtering -- Flexible Voxels for Motion-Aware Videography -- Learning PDEs for Image Restoration via Optimal Control -- Compressive Acquisition of Dynamic Scenes -- Scene Carving: Scene Consistent Image Retargeting -- Two-Phase Kernel Estimation for Robust Motion Deblurring -- Single Image Deblurring Using Motion Density Functions -- An Iterative Method with General Convex Fidelity Term for Image Restoration -- One-Shot Optimal Exposure Control -- Analyzing Depth from Coded Aperture Sets -- We Are Family: Joint Pose Estimation of Multiple Persons -- Joint People, Event, and Location Recognition in Personal Photo Collections Using Cross-Domain Context -- Chrono-Gait Image: A Novel Temporal Template for Gait Recognition -- Robust Face Recognition Using Probabilistic Facial Trait Code -- A 2D Human Body Model Dressed in Eigen Clothing -- Self-Adapting Feature Layers -- Face Recognition with Patterns of Oriented Edge Magnitudes -- Spatial-Temporal Granularity-Tunable Gradients Partition (STGGP) Descriptors for Human Detection -- Being John Malkovich -- Facial Contour Labeling via Congealing -- Cascaded Confidence Filtering for Improved Tracking-by-Detection -- Inter-camera Association of Multi-target Tracks by On-Line Learned Appearance Affinity Models -- Multi-person Tracking with Sparse Detection and Continuous Segmentation -- Closed-Loop Adaptation for Robust Tracking -- Gaussian-Like Spatial Priors for Articulated Tracking -- Dense Point Trajectories by GPU-Accelerated Large Displacement Optical Flow -- Improving Data Association by Joint Modeling of Pedestrian Trajectories and Groupings -- Globally Optimal Multi-target Tracking on a Hexagonal Lattice -- Discriminative Spatial Attention for Robust Tracking -- Object, Scene and Actions: Combining Multiple Features for Human Action Recognition -- Representing Pairwise Spatial and Temporal Relations for Action Recognition -- Compact Video Description for Copy Detection with Precise Temporal Alignment -- Modeling the Temporal Extent of Actions -- Content-Based Retrieval of Functional Objects in Video Using Scene Context -- Anomalous Behaviour Detection Using Spatiotemporal Oriented Energies, Subset Inclusion Histogram Comparison and Event-Driven Processing -- Tracklet Descriptors for Action Modeling and Video Analysis -- Word Spotting in the Wild -- A Stochastic Graph Evolution Framework for Robust Multi-target Tracking -- Spotlights and Posters M2 -- Backprojection Revisited: Scalable Multi-view Object Detection and Similarity Metrics for Detections -- Multiple Instance Metric Learning from Automatically Labeled Bags of Faces -- Partition Min-Hash for Partial Duplicate Image Discovery -- Automatic Attribute Discovery and Characterization from Noisy Web Data -- Learning to Recognize Objects from Unseen Modalities -- Building Compact Local Pairwise Codebook with Joint Feature Space Clustering -- Image-to-Class Distance Metric Learning for Image Classification -- Extracting Structures in Image Collections for Object Recognition -- Size Does Matter: Improving Object Recognition and 3D Reconstruction with Cross-Media Analysis of Image Clusters -- Avoiding Confusing Features in Place Recognition -- Semantic Label Sharing for Learning with Many Categories -- Efficient Object Category Recognition Using Classemes -- Practical Autocalibration.
Keywords: Computer science; Computer software; Computer vision; Computer graphics; Optical pattern recognition; Biometrics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Pattern Recognition; Biometrics; Computer Graphics; Algorithm Analysis and Problem Complexity